2017
DOI: 10.3201/eid2301.161614
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Knowledge among Pregnant Women Who Were in Areas with Active Transmission

Abstract: We surveyed women in New York, New York, USA, who were in areas with active Zika virus transmission while pregnant. Of 99 women who were US residents, 30 were unaware of the government travel advisory to areas with active Zika virus transmission while pregnant, and 37 were unaware of their pregnancies during travel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 3 publications
3
23
1
1
Order By: Relevance
“…Even fewer of the participants knew that ZIKV could be transmitted sexually, consistent with previous studies in other countries [20][23],[27]. Thus, few respondents understood that wearing condoms could prevent transmission.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Even fewer of the participants knew that ZIKV could be transmitted sexually, consistent with previous studies in other countries [20][23],[27]. Thus, few respondents understood that wearing condoms could prevent transmission.…”
Section: Discussionsupporting
confidence: 77%
“…At the time this study was conducted very few studies had assessed knowledge and attitudes of ZIKV. In this study (May 2016), nearly 90% of the Ecuadorian sample had heard of ZIKV, which is higher than in the Nigerian study [21] conducted in September 2016 (68.9%) and a study in the US in March 2016 (85%), but lower than in a follow-up nationally representative US sample (95.0%) conducted in September 2016 [21],[23]. This finding is not surprising since the current ZIKV epidemic started in Brazil and began impacting South and Central American countries before North America.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Of the 1112 cases of definitive Zika virus infections identified in NYC, all have been associated with travel, with nearly half of those cases originating in the Dominican Republic [2,8]. During summer 2016, the number of Zika virus test requests made to the NYC Department of Health and Mental Hygiene by and for women who had traveled to areas with active Zika virus transmission while pregnant increased weekly despite a travel warning being issued months before [9].…”
Section: Introductionmentioning
confidence: 99%
“…10 A second study of 99 pregnant women found that 31% were unaware of the U.S. advisory to avoid travel to active ZIKV outbreak regions and nearly half did not know there was active ZIKV transmission in areas where they had traveled. 11 Neither study included information on women's attitudes or their prevention practices other than limiting travel.…”
Section: Introductionmentioning
confidence: 99%